2002
DOI: 10.1504/ijtm.2002.003080
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation and interfirm cooperation: an exploratory analysis using survey data from manufacturing firms in the metropolitan region of Vienna

Abstract: This paper centres around two research questions: first, the identification of five types of networks that manufacturing firms located in the metropolitan region of Vienna may have created for different purposes; and second, the question to what extent the likelihood of interfirm cooperation is conditioned by the general profile of manufacturing establishments and their technological resources. Although this paper focuses on the manufacturing sector a special emphasis is placed on the electronics industry. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(44 citation statements)
references
References 16 publications
4
37
0
2
Order By: Relevance
“…On the other hand, the current surge in collaborations is another reflection of the fact that technological innovations are less and less the output of an individual firm's isolated efforts (Drejer and Jørgensen, 2006;Fischer and Varga, 2002), which has been particularly highlighted in HT industries (Park et al, 2002;Stuart, 1998). Several recent studies have shown the positive impact of technological collaboration on firms' technological activities and performance (e.g.…”
Section: Beyond Firms' Boundaries: External Sources Of Innovationmentioning
confidence: 99%
“…On the other hand, the current surge in collaborations is another reflection of the fact that technological innovations are less and less the output of an individual firm's isolated efforts (Drejer and Jørgensen, 2006;Fischer and Varga, 2002), which has been particularly highlighted in HT industries (Park et al, 2002;Stuart, 1998). Several recent studies have shown the positive impact of technological collaboration on firms' technological activities and performance (e.g.…”
Section: Beyond Firms' Boundaries: External Sources Of Innovationmentioning
confidence: 99%
“…Innovation is also identified by researchers as one of the main motivations for companies to collaborate (Fischer & Varga, 2002), and to be involved in inter-organizational relationships (Gulati, Nohria, & Zaheer, 2000;Pittaway et al, 2004;Ritter & Gemünden, 2003). Increasingly, a company's capacity to innovate is perceived as being dependent not only on its own internal capabilities and resources, but also on its capacity to integrate and to mobilize (i.e.…”
Section: Network and Networking For Innovationmentioning
confidence: 99%
“…Networking reflects a recognition that technological innovations are less and less the outcome of an individual firm's isolated efforts (Fischer and Varga, 2002;Drejer and Jørgensen, 2005). Despite the increasing number of studies on the effects of networks on firms' technological activities (Miotti and Sachwald, 2003;Belderbos et al, 2004a;Faems et al, 2005;Hoang and Rothaermel, 2005), understanding their impact remains an important and under-researched topic in the literature on management innovation (Amara and Landry, 2005).…”
Section: Introductionmentioning
confidence: 99%